Extraction and purification of antioxidative flavonoids from Chionanthus retusa leaf - Wang, Zhen; Yang, Shilong; Gao, Yajun; Huang, Jianting (Frontiers in Bioengineering and Biotechnology, 2022)
In this work, flavonoids from the leaves of Chionanthus retusa were extracted using alcohol, and the extraction yield was optimized by single-factor and orthogonal experiments. Then, the extracted solution with flavonoids was purified via macroporous resin by elution with different concentrations of ethanol. The antioxidative activity of total flavonoid in purified extracted solution was evaluated by detecting its ability to scavenge DPPH free radicals. The results demonstrated that ethanol with a concentration of 60%, ultrasonic power of 140 W, liquid–solid ratio of 25:1 ml g−1, and water-bath temperature of 80°C were the optimal conditions for the extraction of total flavonoids from C. retusa leaf, achieving a yield of 121.28 mg g−1. After purification by macroporous resin using different concentrations of ethanol, the highest content of total flavonoids (88.51%) in the extracted solution can be obtained with the 50% ethanol eluant. The results of scavenging DPPH free radicals suggest that the purified flavonoids in the 50% ethanol eluant had the best antioxidant capacity over the flavonoids in other ethanol eluants. In addition, it is confirmed the antioxidant capacity of the extractives was associated with the content of total flavonoids and kinds of flavonoids. These results may provide a feasible pathway to make full use of total flavonoids from C. retusa leaf.